Why Does the Poor Glycemic Control Among Type 2 Diabetes Mellitus Patients Remain High in Southeast Asia? - Maria Lisa Nova; Dita Maria Virginia (Sanata Dharma University, 2023)
Presently, as well, 55% of the world’s diabetic population is Asian, with an estimated 230 million. The International Diabetes Federation (IDF) shows that the number of people with diabetes in the Southeast Asia (SEA) Region is 16.8% of all people with diabetes worldwide. To manage a patient’s blood glucose level, consider minimizing the worst effects of diabetes mellitus. Glycemic control using HbA1c levels is one of the important factors in the risk of diabetes that is associated with complications and mortality. A PubMed and Google Scholar databases were searched using the following: We only screened original-type articles for relevance and considered them further. Type 2 diabetes mellitus patients in Southeast Asia mostly experience uncontrolled blood glucose. More than 50% of research subjects show poor glycemic control. The influencing factors of poor glycemic control in Southeast Asia were age, BMI, hypertension, smoking activity, education, physical activity, and dyslipidemia. The awareness of glycemic control must be improved in type 2 diabetes mellitus patients.